1996
DOI: 10.1080/0962029960050114
|View full text |Cite
|
Sign up to set email alerts
|

Information Technology in Initial Teacher Education: preconceptions of history and geography interns, with reflections of mentors and tutors

Abstract: The results of a survey of experiences, feelings and preconceptions concerning information technology (IT) that University of Oxford history and geography interns bring to the one year secondary teacher training course are reported. A notable finding was the significantly greater importance attributed to the use of computers in subject teaching by geography interns compared with historians, and the relatively large numbers of the latter ascribing little or no importance to the use of computers in the teaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Second, the difficulties student teachers face in ICT transfer from higher education institutions (HEIs) to schools. Murphy & Greenwood (1998) highlight difficulties in gaining access to computers, Summers & Easdown (1996) highlight problems of teacher competence while Trushell et al (1995) cite timetabling problems in schools where computer-based teaching is carried out in dedicated computer labs. We believe that if the role of ICT in teaching and learning can be better understood by tutors, students teachers and teachers in schools, then inhibiting factors that influence practice may begin to be eroded.…”
Section: Reflective Learning In the Context Of Ictmentioning
confidence: 99%
“…Second, the difficulties student teachers face in ICT transfer from higher education institutions (HEIs) to schools. Murphy & Greenwood (1998) highlight difficulties in gaining access to computers, Summers & Easdown (1996) highlight problems of teacher competence while Trushell et al (1995) cite timetabling problems in schools where computer-based teaching is carried out in dedicated computer labs. We believe that if the role of ICT in teaching and learning can be better understood by tutors, students teachers and teachers in schools, then inhibiting factors that influence practice may begin to be eroded.…”
Section: Reflective Learning In the Context Of Ictmentioning
confidence: 99%
“…But for the fact that students use of e-learning resources have positive impact in their lives especially creating new ideas, skills, competence and confidence, there is need for the students to have knowledge of e-learning resources. The study of Summers and Easdown (1996), revealed that subject specialization of student could influence their use of e-learning resources.…”
Section: The Measure Of Students' Knowledge Of E-learning Resources Imentioning
confidence: 99%
“…Finally, recent results from Summers & Easdown (1996) indicate that the subject specialism of student teachers may influence the extent of ICT use. Students specialising in geography tended to use computers more in their teaching when compared with students who had chosen history as their main subject.…”
Section: Literature Reviewmentioning
confidence: 99%